Effect of vibro- milling time on phase formation and particle size of ZnNbO6 nano-powders - Athipong Ngamjarurojana (2018)
Zinc niobate, ZnNb2O6, nanopowders was synthesized by a solid-state reaction via a rapid vibro-milling technique. The effect of milling time on the phase formation and particle size of ZnNb2O 6 powder was investigated. The formation of the ZnNb 2O6 phase investigated as a function of calcination conditions by DTA and XRD. The particle size distribution of the calcined powders was determined by laser diffraction technique, while morphology, crystal structure and phase composition were determined via a SEM techniques. In addition, by employing an appropriate choice of milling time, a narrow particle size distribution curve was also observed. © (2010) Trans Tech Publications.